Marketing Strategy in The Development of Rira Dishwashing Soap and Clothes Washing Soap UMKM - Mitasari, Ratna; Nursabrina, Zata Yumni Subhati; Winarno, Agung (Unram Journal of Community Service, 2024)
The importance of MSMEs for the progress of a region, therefore the Sumber Kembar village apparatus agreed to provide direction to residents to be optimistic in running a business and not give up easily if they fail. The purpose of implementing this community service is to create a marketing strategy to improve MSMEs in the community environment. This activity was carried out at the Rira Liquid Soap and Laundry Dishwashing Soap community business, located in Junrejo sub-district, with several stages of activities including initial identification, analysis and planning, mentoring and implementation, and evaluation. The results of this study indicate that Community Service Activities at the "RIRA Dishwashing Soap and Laundry Soap" Business resulted in a NIB Certificate for logo development, a new, more attractive packaging design. Marketing through social media can expand product recognition and marketing reach so that it can increase income from the "RIRA Dishwashing Soap and Laundry Soap" Business which will have an impact on increasing people's purchasing power for household needs, namely dishwashing soap and laundry soap in the Batu city area and its surroundings, especially RIRA Business Owners ". In the future, this business to increase marketing must also be active in using social media